Colombia 2006-2010 : A Window of Opportunity - World Bank (Washington, DC, 2014)
This document presents the recently elected Colombian administration with a set of policy notes meant to enrich the debate around critical issues affecting the country's development. These notes build mostly upon existing research and represent the Bank's independent view on topics which are either at the crux of ongoing policy discussions or merit a more prominent place in this dialogue. This window of opportunity provides a very favorable setting for advancing aggressive interventions to further alleviate poverty and inequality. Even as a country with a long history of solid growth and stable democratic institutions, poverty remains a critical issue for Colombia. Years of consistent economic growth throughout the 1980s and early 1990s lifted many out of poverty, but the macroeconomic crisis at the end of the 1990s eradicated more than a decade of progress. The notes have been grouped around four strategic issues: challenges and constraints for the reform process, investing in people, laying the foundations for competitiveness, and reducing vulnerabilities. To this end, a national strategy for comprehensive peace, reconciliation and equitable development needs to be strengthened with the following elements: (i) a continued national level effort to create incentives for the demobilization of illegal armed groups, (ii) attention to the internally displaced population, who are the most visible and numerous victims of the conflict, (iii) mainstreaming inequality reduction interventions into key sectors, and (iv) local and regional community-led economic development and social capital building plans, inclusive of vulnerable and demobilized populations, all of which would contribute to prevent the recurrence of the armed conflict.